INVESTMENT PROJECT SELECTION BY APPLYING COPRAS METHOD AND IMPRECISE DATA - Gabrijela Popović (Serbian Journal of Management, 2012)
Investment projects can have a significant impact on the functioning and development of acompany. Therefore, the selection of one or more investment projects from the set of possible is animportant and difficult task for decision makers. This paper considers the investment projectsselection based on financial analysis criteria and use of imprecise data. In the proposed model, thealternative projects performances are expressed using crisp and interval values, and then the bestproject from the available is selected by using COPRAS and COPRAS-G methods. A numericalexample is given to demonstrate the applicability and effectiveness of the proposed approach.